Qualitative interview study exploring the perspectives of pregnant women on participating in controlled human infection research in the UK - Christine E Jones; Robert C Read; Tushna Vandrevala; Anastasia A Theodosiou; Robert B Dorey (BMJ Open)
Introduction Pregnant women have been historically excluded from interventional research. While recent efforts have been made to improve their involvement, there remains a disparity in the evidence base for treatments available to pregnant women compared with the non-pregnant population. A significant barrier to the enrolment of pregnant women within research is risk perception and a poor understanding of decision-making in this population.Objective Assess the risk perception and influences on decision-making in pregnant women, when considering whether to enrol in a hypothetical interventional research study.Design Semistructured interviews were undertaken, and thematic analysis was undertaken of participant responses.Participants Twelve pregnant women were enrolled from an antenatal outpatient clinic.Results Participants were unanimously positive about enrolling in the proposed hypothetical interventional study. Risk perception was influenced by potential risks to their fetus and their previous experiences of healthcare and research. Participants found the uncertainty in quantifying risk for new research interventions challenging. They were motivated to enrol in research by altruism and found less invasive research interventions more tolerable.Conclusion It is vital to understand how pregnant women balance the perceived risks and benefits of interventional research. This may help clinicians and scientists better communicate risk to pregnant women and address the ongoing under-representation of pregnant women in interventional research.